Socioeconomic Impact of Tun Sakaran Marine Park: A Descriptive Study of the Perceptions of the Local Community - Lim, Thien Sang; Kasim Md Mansur; Agnes Paulus Jidwin; Azmi Abd Majid; Rostika Petrus Boroh; Rosle Mohidin; Julenah Ag. Nuddin; Kamisan Pusiran (2018)
The study was conducted to gauge the opinions of the local community of Semporna on the establishment of the Tun Sakaran Marine Park. Specifically, the study sought the perceptions of respondents with regard to: (1) socioeconomic impact, (2) development of surrounding areas, and (3) marine conservation and resources. Convenience sampling was employed and data were sourced using a structured questionnaire. Generally, it was concluded that the local community felt the establishment of the Tun Sakaran Marine Park has brought positive impact to the local economic activities. The place experienced good improvement in various economic aspects, particularly tourism related. Although the marine park was perceived as beneficial, its resources were thought to be ineffectively conserved and managed. Despite Semporna gained good reputation as place to enjoy the marine’s beauty, the local community felt that the availability and maintenance of public facilities were somewhat neglected. Thus, study provided recommendations to preserve the sustainability of the area both economically and environmentally.